2021
DOI: 10.1080/1357650x.2021.1898416
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of handedness on the consistency of lateralization for speech production and semantic processing tasks using functional transcranial Doppler sonography

Abstract: The left hemisphere is dominant for language in most people, but lateralization strength varies between different tasks and individuals. A large body of literature has shown that handedness is associated with lateralization: left handers have weaker language lateralization on average, and a greater incidence of atypical (right hemisphere) lateralization; but typically, these studies have relied on a single measure of language lateralization. Here we consider the relationships between lateralization for two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…We theorised that the failure to observe N effects in Experiment 1 may have stemmed from functional differences in left-handers as it is known that left-handers show a greater variability in language lateralisation and a greater incidence of atypical lateralisation than right-handers (e.g. Bruckert et al, 2021;Carey & Johnstone, 2014;Woodhead et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We theorised that the failure to observe N effects in Experiment 1 may have stemmed from functional differences in left-handers as it is known that left-handers show a greater variability in language lateralisation and a greater incidence of atypical lateralisation than right-handers (e.g. Bruckert et al, 2021;Carey & Johnstone, 2014;Woodhead et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…By understanding these processes in skilled readers, it may in turn promote our understanding of reading LATERALISED NEIGHBOURHOOD EFFECTS 7 development and reading disorders. Experiment 1 included left-handed participants only, as it is known that left-handers show a greater variability in language lateralisation and a greater incidence of atypical lateralisation than right-handers (Bruckert, Thompson, Watkins, Bishop, & Woodhead, 2021;Bryden, 1965;Carey & Johnstone, 2014;Kimura, 1973aKimura, , 1973bMazoyer et al, 2014;Rasmussen & Milner, 1977;Woodhead, Thompson, Karlsson, & Bishop, 2021).…”
Section: Lateralised Neighbourhood Effectsmentioning
confidence: 99%
“…For instance, using functional transcranial Doppler sonography, it has been shown that language dominance (using a word-generation task) is linearly correlated with the degree of handedness in healthy individuals (Knecht et al, 2000b;Basic et al, 2004). Other studies have shown that left-handed neurotypical individuals would have weaker lateralization compared to the right-handed group in language tasks (Johnstone et al, 2020;Bruckert et al, 2021;Woodhead et al, 2021). Future studies are required to address the question of whether impairment in human voice processing in ASD individuals is associated with the dominant hemisphere or is simply related to dysfunction in the left hemisphere.…”
Section: Lateralization In Language Associated Auditory Cortical Regi...mentioning
confidence: 99%
“…The papers published in the first issue of Laterality investigated the relationship between handedness and eye-dominance (Bourassa, 1996), attempts to switch the writing hand (Porac, 1996), handedness in professional cricket players (Edwards & Beaton, 1996), and the magnitude of laterality effects and sex differences in functional asymmetries (Voyer, 1996), all topics still of interest today, as shown by recent papers published in Laterality on handedness (e.g., Bruckert, Thompson, Watkins, Bishop, & Woodhead, 2021;Papadatou-Pastou et al, 2021;Tzourio-Mazoyer, Labache, Zago, Hesling, & Mazoyer, 2021) and cognitive sex differences (e.g., Hirnstein, Hugdahl, & Hausmann, 2019).…”
Section: Editorialmentioning
confidence: 99%